(untitled) (Agroindustrial Science, 2020)
This work optimized the temperature and time of pasteurization of purple mashua (Tropaeolum tuberosum Ruíz and Pavón) tubers drink based on its antioxidant capacity, total phenolics, total flavonoids, anthocyanins content, and acceptability. For this, purple mashua tubers from the province of Acobamba-Huancavelica-Peru were weighed, washed, peeled, cut and placed in a juice extractor. The beverage of tubers was prepared using the juice of tubers, the thermal treatment of the samples was carried out at temperatures between 75 to 85 °C and time 10 to 25 min. The design was planned using a Rotational Composite Central Design and a response surface analysis was performed on the samples obtained. The content of total phenolics, anthocyanins, total flavonoids, and antioxidant capacity was influenced by the time and temperature of pasteurization. At higher temperatures and pasteurization times there was a reduction in the content of total phenolics, anthocyanins, total flavonoids, and antioxidant capacity. The greatest general acceptability of the panelists was at high pasteurization temperatures and times. The temperature of 77 °C and time of 13 minutes showed the maximum value of response variables with low degradation of the antioxidant compounds and good acceptability of mashua extract drinks.